2022
DOI: 10.1021/acsami.1c24558
|View full text |Cite
|
Sign up to set email alerts
|

Industrially Compatible Fabrication Process of Perovskite-Based Mini-Modules Coupling Sequential Slot-Die Coating and Chemical Bath Deposition

Abstract: To upscale the emerging perovskite photovoltaic technology to larger-size modules, industrially relevant deposition techniques need to be developed. In this work, the deposition of tin oxide used as an electron extraction layer is established using chemical bath deposition (CBD), a lowcost and solution-based fabrication process. Applying this simple lowtemperature deposition method, highly homogeneous SnO 2 films are obtained in a reproducible manner. Moreover, the perovskite layer is prepared by sequentially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 35 publications
0
29
0
Order By: Relevance
“…Reproduced with permission. 44 Copyright 2022, American Chemical Society. (g) Image for electron chemical deposition (ECD).…”
Section: Solution Processed Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Reproduced with permission. 44 Copyright 2022, American Chemical Society. (g) Image for electron chemical deposition (ECD).…”
Section: Solution Processed Methodsmentioning
confidence: 99%
“…Reproduced with permission. 44 Copyright 2022, American Chemistry Society. (e) Illustration of the electrochemical regulation method (left) and J-V curves of thermal annealed and electrochemical regulated SnO 2 -based mini-modules (right).…”
Section: Solution Processed Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure e,f shows that the dynamic contact angle (θ 1 ) is 45.48° and the surface tension (σ) is 25.007 mN/m between 0.8 M-FA x Cs 1– x PbI 3 and the substrate, respectively. According to the actual experiment in previous achievements, the coating gap ( H ) and the size of slit ( d ) are determined as 80 and 50 μm, respectively . The detailed setting parameters and Carreau fitting results (η 0 , η ∞ , n , and λ) of 0.8 M-FA x Cs 1– x PbI 3 are listed in Table , which are used for subsequent calculations.…”
Section: Simulation and Modelingmentioning
confidence: 99%
“…CBD usually takes a long time to prepare films and requires precise control of the synthesis conditions. [23] E-beam evaporation, as a physical vapor deposition process, has the advantages of low temperature, controllable thickness, and low cost, which benefit mass production and commercial applications. [24,25] It has been reported that TiO x , [26] Nb 2 O 5 , [27] NiO x [28] films were prepared by E-beam evaporation for perovskite photovoltaics.…”
Section: Introductionmentioning
confidence: 99%